The Sperm Olfactory Receptor OLFR601 is Dispensable for Mouse Fertilization - L, González-Brusi; JG, Hamzé; I, Lamas-Toranzo; M, Jiménez-Movilla; P, Bermejo-Álvarez (Frontiers in Cell and Developmental Biology, 2022)
Fertilization involves the fusion of two gametes by means of yet unknown membrane binding and fusion events. Over the last years, a number of sperm proteins have been uncovered to play essential roles on sperm-egg fusion in mammals, but their precise role on fertilization remains unknown, being unclear how these proteins interact with each other or with other yet unknown sperm proteins. The aim of this study has been to identify possible sperm proteins interacting with TMEM95, a protein essential for fertilization located in the sperm membrane. A list of 41 sperm proteins that were pulled down with TMEM95 and identified by mass spectrometry did not include other sperm proteins known to play a role on fertilization, suggesting an independent role of TMEM95 in fertilization. Between this list, OLFR601 is allocated to the acrosomal region and may mediate affinity for an odorant involved in fertilization. However, Olfr601 disruption did not impaired sperm fertilization ability, suggesting that its function may be redundant with that of other sperm proteins.